Diversity of Teleost Leukocyte Molecules: Role of Alternative Splicing - Imarai-Bahamonde, C; Maisey-Munoz, K (2011)
Alternative splicing is an important mechanism of gene expression control that also produces a large proteome from a limited number of genes. In the immune system of mammals, numerous relevant genes have been found to undergo alternative splicing that contributes to the complexity of immune response. An increasing number of reports have recently indicated that alternative splicing also occurs in other vertebrates, such as fish. In this review we summarize the general features of such molecular events in cytokines and leukocyte co-receptors and their contribution to diversity and regulation of fish leukocytes. © 2010 Elsevier Ltd.